Will Chinese external therapy with compound Tripterygium wilfordii hook F gel safely control disease activity in patients with rheumatoid arthritis: design of a double-blinded randomized controlled trial - Quan Jiang; Xiao-Po Tang; Xian-Chun Chen; Hong Xiao; Ping Liu; Juan Jiao (BMC, 2017)
Abstract Background Chinese external therapy (CET) is a topical application with mainly Chinese herb medicine therapy with thousands of years of historical implications and is a clinical routine that is commonly used for relieving joint-related symptoms in patients with arthritis in Chinese hospitals. However, there is a paucity of modern medical evidence to support its effectiveness and safety. Thus, we propose to implement a randomized, double-blinded, placebo-controlled clinical trial in patients with rheumatoid arthritis (RA) using, as the experimental intervention, topical application of a hospital-compounded gel preparation of Tripterygium wilfordii Hook F (TwHF). Methods This study will be an 8-week double-blinded, randomized, placebo-controlled clinical trial conducted at Guang'anmen Hospital in Beijing, China, and 168 patients with moderately active RA will be randomly assigned with a 1:1 ratio to apply a topical gel preparation containing TwHF or placebo. The primary outcome variable will be the proportion of subjects, by study group, to achieve a 20% improvement in the American College of Rheumatology criteria (ACR20) by week 8. Secondary outcome measures to be assessed at weeks 4 or 8 will include: measurement of ACR20 response rate at week 4, ACR50 response rate, the changes in DAS28 score, and joint synovitis classification assessment monitored by musculoskeletal ultrasound. Safety evaluations conducted at weeks 4, 8 and 12 will be based on spontaneous complaints by the study subjects, but special emphasis will be focused on cutaneous allergy and alterations of menstruation in premenopausal female participants. Statistical analyses will be performed using the intention to treat analysis data set. Discussion This proposed clinical trail is designed to evaluate the efficacy and safety of CET based on a single topically-applied agent in a relatively large patient population with RA. This study protocol gives a detailed description of the usage and dosage of the topical compound TwHF gel and the methodology of this study. In addition, it is hoped that the outcomes of this study will be viewed as supporting the generalizability of CET in the setting of inflammatory rheumatic diseases. The results of this study are expected to have important public health implications for Asian RA patients that currently utilize CET as a complimentary treatment. Trial registration Clinical trial gov Identifier: NCT02818361 . Registrated on Jun. 15, 2016.